Strategic choice of freight mode and investments in transport infrastructure within production networks - Ying Yi Tsai (Asian Development Bank Institute (ADBI), 2009)
In the context of production linkages in which downstream producers require freight services provided by transport operators, I show that the strategic choice of using an alternative transport mode does not necessarily induce lower access charges, relative to the standard transport mode. Additionally, I show that the nature of infrastructure investment determines the share of final goods delivery by the alternative transport mode. An immediate implication is that interactions among infrastructure investments; building transportation capacity costs; and industry-specific characteristics should be carefully assessed when planning transport infrastructure investments to enhance competitiveness in export markets.
Keywords: F1; L1; L2; O1; O2; 330